Rainbow trapping of guided waves - Polanco, Javier; Fitzgerald, Rosa M.; Leskova, Tamara A.; Maradudin, Alexei A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We study theoretically the propagation of a wave packet that is a superposition of three s-polarized guided waves with different frequencies in a planar waveguide consisting of a dielectric medium with a graded index of refraction, sandwiched between perfectly conducting walls. The electric field at each point within the waveguide is calculated, and it is shown that each of the constituent modes ceases to propagate at a specific distance along the waveguide that depends on its frequency and on the geometrical and material parameters defining the waveguide. This simple model displays the phenomenon of rainbow trapping of guided waves in an explicit fashion, without the use of a negative index metamaterial.